Molecular Detection of BK Polyomavirus in Patients Under Hemodialysis - Eman Yousuf Rasheed; Fidan Ghanim Reshad; Muhannad Abdullah Allazzawy (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study was conducted in Kirkuk city-Iraq from of February 2018 to September 2018. The numberof chronic kidney disease patients under study were 60 patients whose ages were between 40-70 yearsold. These patients admitted to Kirkuk general hospital (hemodialysis unit). The control group whowere matched to the patients studied, included 30 healthy blood donor and their ages were between 30-75 years old. Blood samples were collected for detection of BK polyomavirus DNA by real time-PCR.The study showed that the highest rate of BK polyomavirus DNA occurrence were recorded in patientswith chronic kidney disease when compared with control group (51.66% versus 3.33%) (P: <0.01).The study showed that the highest mean level of IL-6 was recorded in patients with chronic kidneydisease comparing with the control group (78.42 v.s. 3.40 ng/ml). The result was highly significant. Thepresent study demonstrated that the highest mean level of IL-6 was found in prostates cancer patientswho were positive to BK polyomavirus DNA comparing with BK polyomavirus DNA negative (52.54versus 25.88 ng/ml)It was concluded that BK polyomavirus was frequently detected in chronic kidney disease patients andcould play a relevant role in the development and progression of human hemodialysis